Performance analysis on parallel condensing air-source heat pump water heater system. (July 2022) - Wang, Shouchuan; Wang, Qianxu; Zhang, Huan; Wang, Yuxuan; Zhou, Junhai; Zhao, Panpan; Liu, Jiabao
Abstract: Based on the technology of heat pumps, a parallel condensing air-source heat pumps water heater systems providing domestic hot water is proposed to improve the energy efficiency of common ASHPWH system. Considering the climate in southern China, two operating modes of system are designed to adapt to the different water temperature conditions. the simulation model was built to analyzed the factors affecting system performance. Taking Changsha, China as an example, the COP and the energy consumption of system in each month are analyzed. We can find that the parallel condensing air-sources heat pumps water heater system can effectively disperse the total heating quantity by steps heating; the average COP in summer mode increases from 5.42 to 6.44, approaching 19.00%; the average COP in winter mode increases from 4.05 to 5.45, approaching 34.68%. The system has excellent energy-saving effect especially in winter.